Pengembangan Video Pembuatan Indikator Sintetis untuk Meningkatkan Kompetensi Praktikum Calon Guru Kimia - Ana Mustafidatul Laili; Agus Kamaludin (Jurnal Penelitian Pendidikan IPA, 2023)
The competence to make synthetic indicators is terribly required by chemistry teachers in high school in order that the implementation of practicum can run more effectively and efficiently. This study aimed to develop a practicum video on how to make synthetic indicators and find out the quality of the developed video. This study was a Research and Development (R&D) study with 4D development model (Define, Design, Develop, and Disseminate). The product was a practicum video on how to make synthetic indicators, in the form of MP4, containing the creation of phenolphthalein, starch, Tollens, and Fehling indicators. The product was assessed by one material expert, one media expert, and four reviewers (high school chemistry teachers). The results of product assessments based on quality, from media expert, it got a percentage of 96% in the very good category; from material expert, it got a percentage of 95% in the very good category; and from reviewers, it got a percentage of 98.33% in the very good category. Furthermore, the video was also responded very well by prospective chemistry teachers with an ideal percentage of 98%. Based on the results, it can be concluded that the developed product is feasible to be used in the learning process to improve the ability of prospective chemistry teachers to make synthetic indicators in the laboratory